Loyalitas Nasabah di Bank Mandiri Cabang Kota Jakarta Ditinjau Dari Kualitas Pelayanan Dengan Kepuasan Nasabah Sebagai Variabel Intervening - Faif Yusuf; Syamsudin Syamsudin (Prisani Cendekia, 2023)
The purpose of this study is to analyze customer loyalty in terms of service quality with customer satisfaction as an intervening variable. This type of research uses differential semantic association research. Primary and secondary data are used in this study. Purposive sampling was used in this research sampling technique, resulting in 100 respondents for the research sample. In this study, the structural equation model (SEM) with SmartPLS 3.0 for Windows is used as a data analysis method. Research results show that service quality has a positive and significant effect on customer loyalty, service quality also has a positive and significant effect on customer satisfaction, while customer satisfaction has no significant effect on customer loyalty.